Meta-analysis of plate fixation versus intramedullary fixation for the treatment of mid-shaft clavicle fractures - Zhang, Bing (Scand J Trauma Resusc Emerg Med, 2015)
BACKGROUND: This systematic review and meta-analysis aims to critically compare the outcomes of plate fixation (PF) versus intramedullary fixation (IF) for the treatment of mid-shaft clavicle fractures. METHODS: Relevant original studies were searched in electronic databases of Medline, Embase, Cochrane central database and CNKI (all through October 2014). The study was performed according to the PRISMA statement. Studies that investigated the comparing effectiveness or complications between both groups and provided sufficient data of interest were included in this meta-analysis. RESULTS: Thirteen studies fulfilling inclusion and exclusion criteria were included in this meta-analysis, which included 479 participants in PF group and 457 in IF group. Compared to PFs, IFs outperformed PFs associated with a reduced surgery time, a shorter incision, rapid union time, better shoulder function recovery at 6 months and fewer complications of symptomatic hardware, refracture after hardware removal and hypertrophic scar. In other aspects such as functional recovery at 12 months and 24 months follow-up, shoulder motion range, complications of superficial infection,temporary brachial plexus lesion, nonunion, malunion, delayed union, implant failure, major revision needed, both techniques were comparable. CONCLUSIONS: The present evidence from this meta-analysis suggested that IF was a more advantaged method for the treatment of midshaft clavicle fractures. This present study might aid surgeons in making evidence-based decision about optimal surgical treatment of mid-shaft clavicular fracture. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13049-015-0108-0) contains supplementary material, which is available to authorized users.